Total serum immunoglobulin A in ALS. Issue 1 (2nd January 2021) - Crayle, Jesse; Elmallah, Mai; Sleasman, John; Bedlack, Richard
Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) can have marked phenotypic variability. To date, no biomarker explains this variability. This study tested the hypothesis that immunoglobulin A (IgA) levels might help explain the variability seen in ALS clinical presentations. Methods: A database of the electronic health record at a tertiary referral academic medical center was used to extract data from the charts of patients with ALS-spectrum disease ( n = 489), other neurodegenerative diseases ( n = 174), select chronic autoimmune neurologic diseases ( n = 154), and those neurologically healthy ( n = 17475). Results: There was no significant association of disease and total IgA serum concentrations when controlling for age and sex. No significant association was found between extremes of IgA serum concentrations and various clinical features of ALS. Conclusion: This is the largest study published to-date exploring total serum IgA levels in ALS and provides more conclusive evidence that total serum IgA concentration cannot be used as a standalone biomarker in ALS.